Role of an Interactive Session in the Improvement of Academic Performance in Pre-Clinical Subjects of the Second Year BDS - Atiya Abdul Karim; Nazish Fatima; Sidra Mohiuddin (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objective:  To compare the academic performance of students from two consecutive batches taught through different teaching strategies during their pre-clinical year. Methods: We compare two batches of the second year BDS in a basic dental science subject (a subject I and Subject II). The mode of intervention of the current batch was via interactive lectures compared with didactic lectures delivered to the previous batch. Both batches were assessed by Continuous Assessments Test CAT in mid of semester followed by the Semester Exam. The two-independent t-test was used to measure the difference in academic scores between two batches of students who received teachings through an interactive session and didactic lectures respectively. Results: The students of the current batch (n=41) obtained better scores during the continuous assessment test (65.1±11.01) than (55.3±11.80) previous batch students (n=43) at p<0.001. Similarly, semester exam scores of the current batch were also higher (72.0±8.08) than the previous batch (68.3±9.04) in the subject I at p<0.004. However, in Subject II the academic scores were improved but not statistically significant. Conclusion: It is concluded as, with the interactive sessions academic performance of the current batch has improved as compared to its counterpart.